Health impacts with telework on workers: A scoping review before the COVID-19 pandemic - Furuya, Yuko; Nakazawa, Shoko; Fukai, Kota; Tatemichi, Masayuki (Frontiers in Public Health, 2022)
Background Telework has dramatically increased due to the coronavirus disease 2019 (COVID-19) pandemic, and the health impacts related to telework have become major concerns. Some studies have shown that telework has both positive and negative impacts. However, during the pandemic, the influence of COVID-19 is too strong to estimate the health effects of telework. Therefore, this scoping review investigated a comprehensive overview of those impacts based on studies conducted before the COVID-19 pandemic. Methods We searched keywords related to telework in five databases: PubMed, Scopus, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Cochrane Library, and Ichu-Shi Web. We included articles written in English and Japanese and published from January 2009 to December 2020. One author extracted data, and four authors were paired into two groups. All authors independently conducted the first and second screening and checked the results in pairs. Any disagreements were resolved by reaching a consensus among all authors. All screening and strategies were performed with the consent of all authors. Results Twenty-nine quantitative studies published in 12 countries were extracted. The outcomes included 10 studies on physical and lifestyle outcomes, 25 studies on stress and mental health outcomes, and 13 studies on quality-of-life and wellbeing outcomes. Telework increased sitting time in one study, and two studies showed improvement in behavior, such as reducing smoking or drinking due to telework. While six studies reported subjective stress levels improved by telework, the results for depression, anxiety, and other disorders varied across those studies, and the social or individual factors further complicated the situation. Conclusion Telework is potentially associated with a shift to healthier lifestyles but also the potential for inverse correlation to extend sedentary time. Mental stress indicators depend on the social and individual situations, and very few intervention studies on teleworking existed prior to the COVID-19 pandemic. Our review identified a lack of intervention and comparative research on health problems with telework and revealed a need to conduct research with clear comparisons in post-COVID-19 studies. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021203104, identifier: CRD42021203104.